THE SOCIOLOGICAL UNDERSTANDING OF THE LANGUAGE OF RELIGION: WHAT IS THE WORD ABOUT? - Đorđević, Dragoljub B. (Politikologija religije, 2009)
Respecting its subject matter and its methodological framework, the sociology of religion should solely study the influence of society on religion and that of religion on society. In this process, sociology of religion is much more interested in the results of both influences, which are separated only for analytical reasons, on the group behavior of people - for instance, starting from marital and family life, over other primary and secondary, partial and global groups, all the way to society as a whole - than it is interested in their results on individuals. Sociologists stress that the primary role of the sociology of religion is not to penetrate the “essence of the sacred”. They rather insist on the study of its more mundane ministry. And this earthly substance is that which may be reduced to “socialness”. The sociologically viewed socialness of religion is embodied in the religious community (whether we should technically call it a religious body, group, organization, institution… this is of lesser importance) - which, in terms of development, may be a cult, sect, denomination and church. In it, as an embodied and actual reality, people live their religiosity. If it wishes to be “successful” and behave “appropriately” to its believers, the religious community should address them in a “sociologically intelligible language”. We wish to say that - although it is difficult to distinguish between the transcendental and the mundane ministry of religion - in this author’s view, the sociological understanding of the language of religion is not anything but its “translation”, direction at and accordance with (also) contemporary, even topical, burning issues of the universe, the concrete society, and concrete people being addressed. The responsibility lies with every individual religious organism.